2018
DOI: 10.22456/1679-9216.82554
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Bull on Conception Rate of Dairy Cows in Different Seasons and According to AI Type

Abstract: Background: Reproductive efficiency is one of the most important factors affecting the performance dairy cattle, and fixedtime artificial insemination (TAI) is an important biotechnology factor employed in bovine livestock. The achievement of satisfactory results in TAI protocols depends of several factors, such as health and body condition, milk yield, environmental temperatures, ovulation time, semen manipulation, as well as semen quality. The goal of this study was to evaluate the conception rate of heifers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 10 publications
0
5
0
2
Order By: Relevance
“…However, Schenatto et al (2016) e Luz et al (2018) observed the influence of the bull used in FTAI and concluded that the choice of bulls proved to the technic is a fundamentally important factor to obtain great productive results. Thus, tests are important to determine with certainty the bulls which may have greater performance in FTAI programs, because, as observed by these authors, bulls with approved sperm quality can present different results in the FTAI.…”
Section: Resultsmentioning
confidence: 99%
“…However, Schenatto et al (2016) e Luz et al (2018) observed the influence of the bull used in FTAI and concluded that the choice of bulls proved to the technic is a fundamentally important factor to obtain great productive results. Thus, tests are important to determine with certainty the bulls which may have greater performance in FTAI programs, because, as observed by these authors, bulls with approved sperm quality can present different results in the FTAI.…”
Section: Resultsmentioning
confidence: 99%
“…A data survey using more than 7 thousand inseminations performed in Mato Grosso, Brazil reported by Sá (2012) demonstrated significant differences in CR between samples of semen collected from the same bull in different days. In addition, the effect of the bull on conception may differ depending on the seasons of the year as well as regarding to the parity of the females (Luz et al, 2018). Luz et al (2018) reported a difference of more than 20% in CR when comparing the same bull in different seasons of the year.…”
Section: Discussionmentioning
confidence: 99%
“…According to LE COLZER (2010), heifers undergo puberty when they reach 40% to 50% of adult weight, which normally occurs near 10 months of age and 318 kg of weight on average for the Holstein breed. However, a percentage above of 50% of animals, despite being of adequate age and weight, do not become pregnant after first AI (GONZALES et al, 2015, LUZ et al, 2018, and successive reproductive interventions and are culled without beginning productive life in the farm. The early culling of these animals is detrimental to the system, as heifers are responsible for herd renovation and genetic improvement.…”
Section: Maffi Et Almentioning
confidence: 99%